Uterine rupture secondary to undiagnosed placental site trophoblastic tumor: case report - Hoch, Karin; Tavares, Arthur Antolini; Benetti-pinto, Cristina Laguna; Yela, Daniela Angerame (Brazilian Journal of Oncology, 2022)
Placental site trophoblastic tumor is a rare and malignant form of gestational trophoblastic disease. Its incidence rate is 1/50.000-100.000 pregnancies and accounts for less than 3% of all cases of gestational trophoblastic disease. In addition to its infrequency, the tumor lacks pathognomonic sonographic features, delaying diagnosis until immunohistochemical staining of uterine samples. Early diagnosis is key to avoid metastatic disease. We report a case of an undiagnosed placental site trophoblastic tumor, which caused uterine rupture and hemorrhagic shock.
Keywords: immunohistochemistry; placental site trophoblastic tumor; transvaginal sonography